MODEL KERJASAMA LEMBAGA FILANTROPI DENGAN LEMBAGA KEUANGAN SYARIAH DALAM PROGRAM PEMBERDAYAAN MASYARAKATâ€ - Sarmi Lestari (EPI 16 UMY 063, 2016)

(untitled)
This research aims to understand about the model of philanthropy cooperation with syariah financial institution for public empowerment with cases study in Dompet Dhuafa, BMT Al-Ikhlas and BMT Dana Insani, and the effect of the model of philanthropy in public empowerment program. The method that used in this research is a case study research with qualitative approach. This research is a kind of field research that use a primer data and secondary data which came from Dompet Dhuafa, BMT Al-Ikhlas and BMT Dana Insani. The result shows that model of cooperation that Dompet Dhuafa, BMT Al-Ikhlas and BMT Dana Insani did is getting a syndicate or contract. The Dompet Dhuafa and BMT Al-Ikhlas did the cooperation in the Mitra Pengelola Zakat (MPZ). Since the cooperation of Dompet Dhuafa and BMT Dana Insani are getting Gerai Zakat. The cooperation model of that empowerment gave an effect to increase the public efforts. Index: Model of Cooperation, Philanthropy Institution, BMT